No BRAF V600E Mutation Identified in 28 Periocular Pyogenic Granuloma. Issue 6 (November 2018) - Li, Guosheng; Adams, Emily; Eshleman, James R.; Eberhart, Charles G.
Abstract : Purpose: BRAF V600E mutations were recently identified in some pyogenic granulomas of skin, particularly lesions arising in patients with port wine stains. In this study, the authors analyzed BRAF gene status in 28 periocular pyogenic granulomas to determine its role in their pathogenesis. Methods: Retrospective review of ophthalmic pathology archives from 2007 to 2016 was used to identify pyogenic granulomas of the conjunctiva, eyelid, and orbit. Three eyelid nevi were also analyzed as positive controls. BRAF V600E status was assessed by pyrosequencing of DNA extracted from excess formalin-fixed, paraffin-embedded surgical material. Results: Microscopic examination of the periocular pyogenic granuloma specimens revealed proliferative vascular lesions, with radiating capillary channels surrounded by variable degrees of acute and chronic inflammation. Sequencing did not identify a BRAF V600E mutation in any of the 28 sporadic pyogenic granulomas, including 13 on the eyelid. In contrast, mutation analyses performed in parallel in melanocytic nevi of the eyelid identified BRAF V600E alterations in all 3 cases. Conclusions: The lack of BRAF V600E mutations in 28 sporadic pyogenic granulomas of the conjunctiva and eyelid suggests that such alterations are not a common driver in the pathogenesis of these periocular vascular lesions. Abstract : BRAF alterations have recently been reported in pyogenic granuloma of the skin, but no BRAF V600E mutations were identified in a series of 28 sporadic periocular pyogenic granulomas.